2020
DOI: 10.1136/bmjopen-2020-038030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bright light therapy for depression during pregnancy: a randomised, double-blind controlled trial

Abstract: ObjectivesApproximately 11%–13% of pregnant women suffer from depression. Bright light therapy (BLT) is a promising treatment, combining direct availability, sufficient efficacy, low costs and high safety for both mother and child. Here, we examined the effects of BLT on depression during pregnancy.DesignRandomised, double-blind controlled trial.SettingPrimary and secondary care in The Netherlands, from November 2016 to March 2019.Participants67 pregnant women (12–32 weeks gestational age) with a DSM-5 diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 77 publications
(92 reference statements)
0
14
1
2
Order By: Relevance
“…BLT, also known as phototherapy, uses glare therapy in the treatment of the symptoms of depression [367][368][369][370][371][372][373][374]. Some research studies have reported that BLT was successful as an adjunctive therapy for BD [375][376][377][378][379][380].…”
Section: Bltmentioning
confidence: 99%
“…BLT, also known as phototherapy, uses glare therapy in the treatment of the symptoms of depression [367][368][369][370][371][372][373][374]. Some research studies have reported that BLT was successful as an adjunctive therapy for BD [375][376][377][378][379][380].…”
Section: Bltmentioning
confidence: 99%
“…In this regard, the antidepressant effects of the higher‐intensity placebo lights used in these studies remain unclear, considering that illuminance levels as low as 100 lux have been demonstrated to phase‐shift human circadian rhythms 10 . In fact, in a recent RCT examining the effectiveness of BLT (9′000 lux, 5′000 K) versus DRL (100 lux, 2′700 K) for 6 weeks, 30 min in the morning after awakening, in a larger sample of pregnant women with AND ( n = 67), Bais et al did not find statistically significant differences between the two treatment groups, with a similar improvement in median depression scores on the SIGH‐SAD, HDRS, and Edinburgh Postnatal Depression Scale (EPDS) at the end of the trial, 3 and 10 weeks after therapy, as well as 2 months postpartum 5 . By contrast, Wirz‐Justice and colleagues using a similar protocol for BLT (7′000 lux, for 6 weeks, 60 min in the morning, n = 16) as in Epperson et al but a lower‐intensity placebo light (70 lux, n = 11), found that women with AND who received BLT had significantly greater scores improvement on the SIGH‐ADS and HDRS than those in the DRL group 11 .…”
Section: Introductionmentioning
confidence: 93%
“…Bright light therapy (BLT) is a non‐pharmacological intervention based on circadian science, which has been consistently proven effective and safe for treating seasonal and non‐seasonal affective disorders 3 . However, only a few studies have used BLT in either antenatal or postnatal depression, with overall promising but partly divergent findings 4,5 . Five of them were randomised controlled trials (RCT) and two were open trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ŠT nėra susijusi su jokia reprodukcine rizika, šviesos taikymas nėštumo metu yra saugus, tačiau ją taikyti draudžiama manijos, hipomanijos ar mišrios nuotaikos epizodų metu. Šalutinis ŠT poveikis yra galvos skausmas, pykinimas ir nervingumas [29].…”
Section: Bipolinio Sutrikimo Valdymas Nėštumo Ir Pogimdyminiu Laikotarpiuunclassified